The effect of grinding size and amylase enzyme supplementation on potential ruminal and total tract starch digestion of maize in dairy cows - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2024)
Dissertation (MSc (Agric) Animal Nutrition)--University of Pretoria, 2023.